Using reward mechanism to encourage learners’ motivation: an investigation of learning management system (LMS) features - Nordin, Azlin (2024)
The integration of badges in LMS has emerged as an innovative strategy to enhance learner motivation and engagement. Badges can be awarded to learners for completing tasks, demonstrating skills, or reaching milestones within an educational environment. A study by Abramovich et al. (2013) found that badges can significantly increase student engagement, particularly when the badges are perceived as meaningful and linked to relevant learning outcomes. ​Incorporating digital badges as a reward mechanism in education not only motivates ​learners but also creates a more engaging and inclusive learning environment, thus fostering a culture of achievement and continuous improvement.